2020
DOI: 10.3390/ijms21113776
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and the Uterine Immune Cell Landscape: The Shaping Role of Inflammation

Abstract: Inflammation is often equated to the physiological response to injury or infection. Inflammatory responses defined by cytokine storms control cellular mechanisms that can either resolve quickly (i.e., acute inflammation) or remain prolonged and unabated (i.e., chronic inflammation). Perhaps less well-appreciated is the importance of inflammatory processes central to healthy pregnancy, including implantation, early stages of placentation, and parturition. Pregnancy juxtaposed with disease can lead to the perpet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 241 publications
1
32
0
2
Order By: Relevance
“…Obesity-driven inflammation has further shown associations with trophoblast development and function in animal models, where leptin and low-density lipoproteins are able to regulate trophoblast apoptosis, proliferation, and migration in culture [ 2 ]. Consistently, high-fat-fed animals showed impaired uterine vascular remodeling, placental angiogenic defects, poor decidualization, and smaller implantation site in obese early pregnancy [ 41 , 42 ].…”
Section: Pathobiology Of Maternal Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity-driven inflammation has further shown associations with trophoblast development and function in animal models, where leptin and low-density lipoproteins are able to regulate trophoblast apoptosis, proliferation, and migration in culture [ 2 ]. Consistently, high-fat-fed animals showed impaired uterine vascular remodeling, placental angiogenic defects, poor decidualization, and smaller implantation site in obese early pregnancy [ 41 , 42 ].…”
Section: Pathobiology Of Maternal Obesitymentioning
confidence: 99%
“…Human studies confirmed the role of several adipokines (i.e., leptin) in regulating placental angiogenesis, protein synthesis, and growth, finally impacting placental function in obese mothers [ 43 , 44 ]. Transcriptomic analyses of human obese placentas confirmed an increased expression of genes related to lipid metabolism, angiogenesis, and hormone/cytokine activity, resulting in a lipotoxic placental environment characterized by decreased vasculogenesis, increased oxidative stress, and fetoplacental hypoxia [ 2 , 45 ]. Moreover, placental metabolome analysis of obese pregnancies has also recently shown different patterns of amino acid profiles and mitochondrial function, supporting a shift towards higher placental metabolism.…”
Section: Pathobiology Of Maternal Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term presence of these pro-inflammatory factors not only induces systemic inflammation but also gives a rise to immune cell alterations at distal organ sites, leading to multi-organ dysfunction ( 17 ). Therefore, it is unsurprising that obesity-related stress alters the immune environment at the maternal–fetal interface, disrupting normal placental function which can lead to pregnancy failure ( 18 ). Several reported studies appear to verify this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that inflammation, rather than obesity per se, affects the risk of adverse outcome [ 5 , 6 ]. Specifically, it is hypothesized that increased adipose tissue results in elevated levels of pro-inflammatory cytokines in the blood [ 7 , 8 , 9 ], which influence the function of immune cells within the uterus [ 5 ], thereby impairing normal placental development and increasing the risk of adverse outcomes [ 10 , 11 ]. While maternal obesity alone does not necessarily lead to complications, the associated chronic, low-grade inflammation might increase susceptibility to adverse outcomes when combined with an additional inflammatory challenge.…”
Section: Introductionmentioning
confidence: 99%